(untitled) (Research, Society and Development, 2019)
The significant importance of Conservation Units (CUs) for the environment is intrinsically associated with their relevant role as an instrument for the application of public environmental policies that allows the management of protected areas, prioritizing the preservation of their natural resources, biodiversity and scenic beauty. The CUs public use is related to the occurrence of leisure, recreational, sports, tourist, educational, scientific, environmental interpretation activities that characterize the units’ public visitation and represent the urban society’s interaction with nature and with the principles of preservationism. However, CUs public use when poorly planned and inefficiently supervised may be the source of negative impacts to ecosystems in conservation areas. The objective of this work is to present a study in which the scientific production related to the impacts of public use in CUs of the State of Rio de Janeiro. For such was carried out a survey of the works contained in the annals of Encontro Fluminense – Uso Público de Unidades de Conservação, promoted by the UFF and the Simpósio de Gestão Ambiental e Biodiversidade Fluminense, carried out by UFRRJ, related to 2012 to 2017 editions. This research focused on the investigation of negative aspect impacts in this areas. The selective criteria for the paper’s selection was based on the identification specific title’s terms, on keywords used by the researchers and on abstracts’ reading. The methodology applied in this study was documentary research and analysis. The data collected were analyzed quantitatively and qualitatively and categorized as their approach to the theme impacts of public use. Among events’ annals, a total of 21 papers were found by the selection criteria defined to research for documents associated with the central theme. The results obtained indicate a broad scope of public use in CUs that allows the production of several types of research, covering several topics such as public use impacts evaluation, identification and mapping of cover and land use types, definition of units’ visitor profiles, Environmental Education programs, that despite proposing different study objects make a great contribution to the purpose of environmental conservation associated with the implementation of Conservation Units.